Fortaleza nos primeiros tempos da TV: cotidiano, memória e cultura (1958-1965) - Quezado, Ana Leopoldina Macedo (2007)
The purpose of this paper is to ponder the first days of television in Fortaleza´s everyday life since the preliminary movements towards the set up of the pioneer TV station, TV Ceará. This period of time started in 1958; going through 1960 with the inauguration of the broadcast, where its programs were produced locally; until 1965 with the arrival of the videotape programs produced in Rio de Janeiro and São Paulo. For this work I used the methodology from Oral History to be able to interpret the memories told by people who lived in Fortaleza during the period I have studied, making evident the daily schemes and social experiences, marked by complexity and studded with historically located conflicts. I consider that, despite the individual recollections related to their times and life, the memories registered from each one of those who gave evidence, have elements that are common to other people who were present at the same time. I have also searched newspapers and magazines to “investigate” how the insertion of the TV station, as part of the so-called cultural industry, have altered the dynamics of the state´s capital, marking the moments where it was present impelling new habits and customs as well as giving origin to spaces of sociability.